The Neglected Discipline of Almsgiving - Harrod, Joseph C. (Journal of spiritual formation & soul care, 2019)
Though the early church practiced almsgiving as a normative act of piety its role as a formative spiritual discipline has been largely ignored in contemporary evangelical works on the disciplines. In this article, I argue that intentional and real care for the poor, though rarely mentioned today as a formative practice in evangelical circles, ought to be included in normative discussions of the spiritual disciplines.